Epidemiology of Clostridium difficile infections in a tertiary‐care hospital in Korea. (19th June 2012) - Kim, J.; Kang, J. O.; Kim, H.; Seo, M.‐R.; Choi, T. Y.; Pai, H.; Kuijper, E. J.; Sanders, I.; Fawley, W.
Abstract To survey healthcare‐associated Clostridium difficile infection (HA‐CDI) in a 900‐bed tertiary‐care hospital, we prospectively investigated the epidemiology of CDI and distribution of PCR‐ribotypes. From February 2009 through January 2010, all patients with HA‐CDI were enrolled. Epidemiological information and prescription records for antibiotics were collected. The C. difficile isolates were characterized using reference strains and were tested for antibiotic susceptibility. During the survey, incidence of HA‐CDI was 71.6 per 100 000 patient‐days. In total, 140 C. difficile isolates were obtained from 166 patients with HA‐CDI. The PCR‐ribotyping yielded 38 distinct ribotypes. The three most frequently found ribotypes made up 56.4% of all isolates; they comprised 37 isolates (26.4%) of PCR‐ribotype 018, 22 (15.7%) of toxin A‐negative PCR‐ribotype 017, and 20 (14.3%) of PCR‐ribotype 001. Clostridium difficile PCR‐ribotype 018 was present in all departments throughout the hospital during the 11 months, whereas ribotype 017 and ribotype 001 appeared mostly in the pulmonary department. Hypervirulent C. difficile PCR‐ribotype 027 was detected in 1 month on two wards. The incidence of CDI in each department showed a seven‐fold difference, which correlated significantly with the amount of prescribed clindamycin (R = 0.783, p 0.013) or moxifloxacin (R = 0.733, p 0.025) in the departments. The rates of resistance of the three commonest ribotypes to clindamycin and moxifloxacin were significantly higher than those of other strains (92.1% versus 38.2% and 89.5% versus 27.3%, respectively). CDI is an important nosocomially acquired infection and this study emphasizes the importance of implementing country‐wide surveillance to detect and control CDI in Korea.